Microsphere as a Novel Drug Delivery System : A Review (International Journal of Scientific Research in Science and Technology, 2024)
Microspheres play a very important role as particulate drug delivery system because of their small size and other efficient properties. Microspheres have been proved to be a suitable bridge to scale the distance over to formulate an effective dosage form, to simulate controlled drug release. Microspheres are characteristically free flowing solid powders, which consist of proteins or synthetic polymer, which are biodegradable in nature[1]. Microsphere size ranges Between 1 to 1000 um . It can be administered By oral, Parentral ,Transdermal, ophthalmic, nasal ,colonal routes etc. Microspheres received much attention not only for prolonged release, but also for targeting of anticancer drugs. In future by combining various other strategies, microspheres will find the central place in novel drug delivery, particularly in diseased cell sorting, diagnostics, gene & genetic materials, safe, targeted and effective in vivo delivery and supplements as miniature versions of diseased organ and tissues in the body[2]